Augustine's Hermeneutics and Postmodern Criticism - Young, Frances M. (Interpretation, 2004)
Did Augustine anticipate postmodern criticism, particularly in his theory of signs? While there are superficial similarities, Augustine's position is fundamentally invested in issues of truth and reference that postmodernism brackets out.